Millimeter wave antennas for 5G mobile terminals and base stations - Koul, Shiban Kishen; Karthikeya, G.S. (Boca Raton : CRC Press, 2021)
'This book gives a comprehensive idea of the recent research efforts targeting mmWave 5G mobile terminals and base stations. This is followed by conformal antennas which could be easily integrated onto typical smartphones'--
Includes bibliographical references and index.
Keywords: Antennas (Electronics) -- Design and construction; Millimeter wave devices; Mobile communication systems